2019
DOI: 10.1038/s41598-019-39570-y
|View full text |Cite
|
Sign up to set email alerts
|

FCC to BCC transformation-induced plasticity based on thermodynamic phase stability in novel V10Cr10Fe45CoxNi35−x medium-entropy alloys

Abstract: We introduce a novel transformation-induced plasticity mechanism, i . e ., a martensitic transformation from fcc phase to bcc phase, in medium-entropy alloys (MEAs). A VCrFeCoNi MEA system is designed by thermodynamic calculations in consideration of phase stability between bcc and fcc phases. The resultantly formed bcc martensite favorably contributes to the transformation-induced plasticity, thereby leading to a significant enhancement in both strength and ductil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…As mentioned above, ε-martensite plates can act as one of the nucleation sites of α ' -martensite during plastic deformation [25]. This phenomenon was reported by Jo et al [27] where they observed nucleation of bcc phases on the hcp phases in the V 10 Cr 10 Fe 45 Co 30 Ni 5 alloy system. A similar phenomenon is observed in the present study where α ' -martensite (bcc) is nucleated inside DTs where the ε-martensite (hcp) has already been formed as shown in Fig.…”
Section: Phase Transformationmentioning
confidence: 52%
“…As mentioned above, ε-martensite plates can act as one of the nucleation sites of α ' -martensite during plastic deformation [25]. This phenomenon was reported by Jo et al [27] where they observed nucleation of bcc phases on the hcp phases in the V 10 Cr 10 Fe 45 Co 30 Ni 5 alloy system. A similar phenomenon is observed in the present study where α ' -martensite (bcc) is nucleated inside DTs where the ε-martensite (hcp) has already been formed as shown in Fig.…”
Section: Phase Transformationmentioning
confidence: 52%
“…Crystallographic data ICSD-52258 were used to calculate the XRD profile of Fe-bcc ( a Fe = 2.8665 Å), while ICSD-44387 was used for Ag-fcc ( a Ag = 4.0855 Å). Note that a fcc structure can be thought as an expanded bcc structure along the c -axis by a factor of , , such that the two crystal structures satisfy the relation , which complicate XRD characterization because the XRD profile of bcc-Fe is very similar to the subset of polycrystalline fcc-Ag up to 2θ > 130° with a difference Δ­(2θ) < 1.5°, as seen in the simulated XRD profiles for this transition in Figure S9. However, as seen in Figure b,d, Fe-bcc and Ag-fcc exhibit preferred orientations along the close-packed (110) and (111) planes, respectively, so that it is still possible to use XRD to distinguish Fe from Ag phases.…”
Section: Resultsmentioning
confidence: 99%
“…However, the emergence of non-equiatomic HEAs have shown new possibilities in terms of exploring mechanical properties and phase stability of these alloys. Many of the reported non-equiatomic HEAs were metastable, and facilitate phase transformation under externally applied stress, thus resulting in the TRIP effect 22 , 23 . TRIP assisted deformation of FCC-HEAs and BCC-HEAs have been actively studied recently 13 , 24 27 .…”
Section: Discussionmentioning
confidence: 99%